Stereotactic MR-guided online adaptive radiation therapy (SMART) for the treatment of liver metastases in oligometastatic patients: initial clinical experience - Ugurluer, Gamze; Mustafayev, Teuta Zoto; Gungor, Gorkem; Atalar, Banu; Abacioglu, Ufuk; Sengoz, Meric; Agaoglu, Fulya; Demir, Gokhan; Ozyar, Enis (KOREAN SOC THERAPEUTIC RADIOLOGY \& ONCOLOGY, 2021)
Purpose: We aimed to present our initial clinical experience on the implementation of a stereotactic MR-guided online adaptive radiation therapy (SMART) for the treatment of liver metastases in oligometastatic disease. Materials and Methods: Twenty-one patients (24 lesions) with liver metastasis treated with SMART were included in this retrospective study. Step-and-shoot intensity-modulated radiotherapy technique was used with daily plan adaptation. During delivery, real-time imaging was used by acquiring planar magnetic resonance images in sagittal plane for monitoring and gating. Acute and late toxicities were recorded both during treatment and follow-up visits. Results: The median follow-up time was 11.6 months (range, 2.2 to 24.6 months). The median delivered total dose was 50 Gy (range, 40 to 60 Gy)

with a median fraction number of 5 (range, 3 to 8 fractions) and the median fraction dose was 10 Gy (range, 7.5 to 18 Gy). Ninety-three fractions (83.7\%) among 111 fractions were re-optimized. No patients were lost to follow-up and all patients were alive except one at the time of analysis. All of the patients had either complete (80.9\%) or partial (19.1\%) response at irradiated sites. Estimated 1-year overall survival was 93.3\%. Intrahepatic and extrahepatic progression-free survival was 89.7\% and 73.5\% at 1 year, respectively. There was no grade 3 or higher acute or late toxicities experienced during the treatment and follow-up course. Conclusion: SMART represents a new, noninvasive and effective alternative to current ablative radiotherapy methods for treatment of liver metastases in oligometastatic disease with the advantages of better visualization of soft tissue, real-time tumor tracking and potentially reduced toxicity to organs at risk.
Keywords: Liver; Metastases; Oligometastatic disease; Stereotactic radiation therapy; MRI; Image guidance